Tranexamic Acid: When is It Indicated in Orthopaedic Surgery? - Viberg, Bjarke (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Tranexamic acid (TXA) has been studied extensively during the last 5–8 years. It inhibits clot dissolution during surgery and can therefore reduce blood loss. However, there has been concern that this could result in more frequent complications, specifically in terms of thromboembolic events. The indications for TXA are widespread, and this review covers the literature on orthopaedic indications such as joint replacement, fracture surgery, and arthroscopic procedures. In general, TXA is safe and can be used in a wide variety of orthopaedic procedures, lowering blood loss without increasing the risk of complications.
Keywords: Tranexamsäure; orthopädische Chirurgie; Transfusion; Blutverlust; Thromboembolie; Gelenkersatz; Fraktur; Arthroskopie